PERSEPSI TENTANG KARAKTERISTIK DOSEN TERHADAP MOTIVASI BELAJAR MAHASISWA - Dede Mustomi (Universitas Bina Sarana Informatika, 2018)
This paper investigates on student perception of characteristics lecturers. The lecture is one of the oldest and, maybe still, the most widely used teaching method in tertiary educational institutions. It has been a primary component in the teaching and learning programmes of Universities since the very early days of university education (Bligh, McKeachie in Marmah 2014). Perception is a process whereby individuals organize and interpret their impression of sensory impression to give meaning to their environment (Robbins and Judge, 2009). The character is understood as the level of power in which the individual is able to handle the condition (Koesoema in Manalu 2014). The research method used descriptive research method. Data collection techniques in this study by questionnaire. Sampling technique in this research using simple random sampling technique. This research is conducted in BSI Cibitung with respondent amount 49 personnel of student. The objectives of this research was to find out student perception of lecturers characteristics.